Biomechanical effects of six internal fixation methods for distal femoral AO/OTA 33C1 fractures: finite element analysis - Jianxiong Zhang; Jiadi Le; Zhenghao Wu; Long Chen (BMC Musculoskeletal Disorders)
Abstract Purpose Using finite element analysis, to compare the stress and deformation of six different internal fixation methods for distal femoral fractures to obtain the optimal internal fixation method. Methods Create six groups based on different placement methods and fixation methods: 5-hole lateral plate (SP); 5-hole lateral plate + two medial screws (SP + D); 5-hole lateral plate + one trans-plate screw (SP + O); 5-hole lateral plate + one cross screw (SP + C); 5-hole lateral plate + elastic nail (SP + S); 5-hole lateral plate + medial T-shaped plate (SP + T). Observe the displacement distribution and maximum displacement at the fracture site, and stress distribution on the medial fracture fragment and internal fixation. Results After applying the load, mechanical indicators for internal fixation and bone blocks were obtained for all six models by finite element method. The model with a lateral single plate showed max internal fixation stress of 221.75 MPa, which was greater than other models. On the other hand, the model with a 5-hole lateral plate and medial T-shaped plate showed the smallest internal fixation stress (125.74 MPa) and the smallest total femoral deformation (0.99416 mm). Conclusion The combination of a 5-hole lateral plate and a medial T-shaped plate demonstrated significant biomechanical advantage compared to the other five groups. Although the 5-hole lateral plate model is slightly inferior compared to the 5-hole lateral plate and medial T-shaped plate, it remains an effective and safe fixation solution for AO/OTA 33C1 type fractures.